Antioxidant Vitamin Supplementation Reduces Benzo(a)pyrene-DNA Adducts and Potential Cancer Risk in Female Smokers - Mooney, LaVerne A.; Madsen, Ann M.; Tang, Deliang; Orjuela, Manuela A.; Tsai, Wei-Yann; Garduno, Elizabeth R.; Perera, Frederica P. (Cancer epidemiology, biomarkers & prevention, 2005)
Background: Elevated benzo( a )pyrene [B(a)P]-DNA adducts have been associated with 3-fold increased risk of lung cancer in current smokers. We assessed the chemopreventive effects of antioxidant supplementation using B(a)P-DNA adducts in leukocytes as an intermediate cancer risk marker. Methods: Subjects were randomized to a double-blinded placebo-controlled clinical trial of antioxidant vitamin supplementation [500 mg vitamin C and 400 IU vitamin E ( dl -α-tocopherol) daily] or placebo. Smokers with ≥10 cigarettes per day and serum cotinine ≥25 ng/mL were eligible for the study. B(a)P-DNA adduct level was the outcome. The randomization was stratified by gender and cigarettes per day (≤20 or >20). Smoking habits and blood samples were collected every 3 months during the 15-month treatment period. Samples were analyzed for B(a)P-DNA adducts (high-performance liquid chromatography), plasma cotinine, vitamin levels, and GSTM1 genotype. The intent-to-treat model adjusted for B(a)P-DNA and cotinine at randomization. Results: Overall and among men, there was no effect of treatment on B(a)P-DNA adduct levels. Among treated women, B(a)P-DNA adducts decreased by 31% compared with women on placebo ( P = 0.03). Among treated women with the GSTM1 genotype, there was a 43% decrease in adducts ( P = 0.04). Conclusion: Our primary hypothesis that the mean level of smoking-related B(a)P-DNA adducts would be lower in all subjects in the vitamin treatment group compared with all placebo-treated subjects was not substantiated. However, oursecondary gender-specific analysis found a significant reduction in B(a)P-DNA adducts in women with vitamin treatment, suggesting that antioxidant supplementation maymitigate some of the procarcinogenic effects of exposuretoB(a)P. The effect in GSTM1-null women suggeststhat certain subgroups may derive more benefit fromsupplementation. Although the results of this trial showthe potential chemopreventive role of antioxidants, thebest way for smokers to reduce their cancer risk remains smoking cessation.